Early oral feeding after pancreatoduodenectomy enhances recovery without increasing morbidity. Issue 7 (6th December 2013) - Gerritsen, Arja; Wennink, Roos A. W.; Besselink, Marc G. H.; van Santvoort, Hjalmar C.; Tseng, Dorine S. J.; Steenhagen, Elles; Borel Rinkes, Inne H. M.; Molenaar, I. Quintus
Abstract Objective The aim of this study was to evaluate whether a change in the routine feeding strategy applied after pancreatoduodenectomy (PD) from nasojejunal tube (NJT) feeding to early oral feeding improved clinical outcomes. Methods An observational cohort study was performed in 102 consecutive patients undergoing PD. In period 1 (n = 51, historical controls), the routine postoperative feeding strategy was NJT feeding. This was changed to a protocol of early oral feeding with on‐demand NJT feeding in period 2 (n = 51, consecutive prospective cohort). The primary outcome was time to resumption of adequate oral intake. Results The baseline characteristics of study subjects in both periods were comparable. In period 1, 98% (n = 50) of patients received NJT feeding, whereas in period 2, 53% (n = 27) of patients did so [for delayed gastric empting (DGE) (n = 20) or preoperative malnutrition (n = 7)]. The time to resumption of adequate oral intake significantly decreased from 12 days in period 1 to 9 days in period 2 (P = 0.015), and the length of hospital stay shortened from 18 days in period 1 to 13 days in period 2 (P = 0.015). Overall, there were no differences in the incidences of complications of Clavien–Dindo Grade III or higher, DGE, pancreatic fistula, postoperative haemorrhage and mortality between the two periods. Conclusions The introduction of an early oral feeding strategy after PD reduced the time to resumption of adequate oral intake and length of hospital stay without negatively impacting postoperative morbidity.